A novel platform for detection of protooncogene based on Au nanocluster enhanced fluorescence. Issue 1 (25th November 2014) - Mao, Kang; Liu, Yizhen; Xiao, Huaming; Chen, Yinran; Wu, Zitong; Zhou, Xiaodong; Shen, Aiguo; Hu, Jiming
Abstract : For the first time, gold nanoclusters were found to exhibit high fluorescence enhancement ability based on the metal-enhanced fluorescence (MEF) effect, which can effectively enhance the fluorescence of fluorescein isothiocyanate (FITC). Abstract : For the first time, gold nanoclusters were found to exhibit high fluorescence enhancement ability based on the metal-enhanced fluorescence (MEF) effect, which can effectively enhance the fluorescence of fluorescein isothiocyanate (FITC). By means of this phenomenon, Au nanoclusters have been successfully used in the construction of a fluorescence-enhanced sensing platform for the detection of protooncogene.